(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Diabetes mellitus (DM) is a complex metabolic disease that disrupts the biological environment through a number of deleterious molecular pathways and cellular abnormalities. It is currently a growing global health concern and this study investigated the relationship between vitamin D deficiency and high blood sugar. Blood samples were collected from people in the hospital and analyzed to measure vitamin D levels and fasting blood sugar levels. They found that men had significantly higher vitamin D levels than women. There were no statistically significant differences in fasting blood sugar levels between men and women. Overall, the study suggests that men may be less likely to develop vitamin D deficiency than women, but it did not find a .clear link between vitamin D levels and fasting blood sugar